DFNA5 (ICERE-1) contributes to acquired etoposide resistance in melanoma cells - Lage, Hermann; Schadendorf, Dirk (FEBS letters, 2001)
Resistance to drug treatment is a common observation in malignant melanoma. In order to analyze alterations in mRNA expression profiles associated with drug resistance in melanoma cells we previously established a panel of various drug-resistant cell variants derived from the human melanoma line MeWo and compared the mRNA expression profiles by a differential display technique. By that approach it could be demonstrated that the expression level of a mRNA encoded by a gene found to be mutated in non-syndromic hearing impairment, DFNA5 (ICERE-1), was distinctly decreased in the 33-fold etoposide-resistant melanoma cell line MeWo ETO 1. To evaluate the hypothesis that a decrease in DFNA5 mRNA expression level contributes to the acquired etoposide resistance phenotype exhibited by MeWo ETO 1 cells, this drug-resistant line was stably transfected with the DFNA5-encoding cDNA. Transfected clones showed a 30-35% reduced etoposide susceptibility by comparing the IC25, IC50 and IC75 values of these clones with those displayed by the non-transfected, etoposide-resistant melanoma cell line MeWo ETO 1 and controls. Furthermore, etoposide exposure of stable DFNA5 transfectants resulted in an increase of caspase-3-mediated apoptotic events in DFNA5-transfected clones in comparison to MeWo ETO 1 cells and controls. The data therefore demonstrate that a decrease in DNFA5 mRNA expression level is associated with an increased etoposide resistance in melanoma cells due to an elevated cellular susceptibility to trigger a caspase-3-depending signal pathway leading to programmed cell death.